A study of high sensitive C-reactive protein in rheumatoid arthritis patients - Meena, Priyanka; Goswami, Sourabh; Mathur, Ajay; Sharma, Ramji (International Journal of Research in Medical Sciences, 2020)
Background: Rheumatoid arthritis (RA) is not only merely limited to joints but has many extraarticular features. The major cause of mortality in RA is cardiovascular disease (CVD). Inflammation in RA predispose them to succumb to CVD. The aim of this study to observe whether therapy with disease-modifying anti-rheumatic drugs (DMARD) decreases inflammation and if it does so than it can be said that decrease the risk to develop CVD. Aim and objectives were to assess hs-CRP level in early and established RA both at diagnosis and again at 3 months of DMARD therapy and compare between them. Methods: Total 58 early RA (group A) and 58 established (group B) DMARD naïve RA patients were included in the study. Age, BMI, haemoglobin, random blood sugar, lipid profile, ESR, hs-CRP, RA factor and anti-CCP were measured. All of them were treated with DMARD and hs-CRP was again assessed after 3 months. Results: The mean hs-CRP level at diagnosis was 6.14±1.90 mg/l in group A while it was 10.39±3.13 mg/l in group B. The mean hs-CRP level after 3 months of DMARD was 2.56±1.35mg/l in group A while it was 7.91±3.13 mg/l in group B. The mean reduction in hs-CRP level in early RA (3.58±0.99 mg/l) was statistically significantly (p<0.001) higher than that in established RA (2.48±0.09 mg/l). Conclusions: DMARD decreases level of inflammation in RA more efficiently if initiated early in the course of the disease.